2022
DOI: 10.3390/metabo12080734
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Biomarker Model for Predicting Preterm Birth in Cervicovaginal Fluid

Abstract: Preterm birth (PTB) is a social problem that adversely affects not only the survival rate of the fetus, but also the premature babies and families, so there is an urgent need to find accurate biomarkers. We noted that among causes, eubiosis of the vaginal microbial community to dysbiosis leads to changes in metabolite composition. In this study, short chain fatty acids (SCFAs) representing dysbiosis were derivatized using (N-tert-butyldimethylsilyl-N-methyltrifluoroacetamide, MTBSTFA) and targeted analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…The selected lipid biomarkers were significantly reduced in PTB conditions ( Figure 6 ). According to the results of previous research in our laboratory, polar metabolites increase in PTB [ 28 ], but most of the lipid biomarkers tend to decrease in PTB. Among the phospholipids selected as biomarkers, not only PCs and PEs, but also PlsPCs and PlsPEs, were decreased in preterm birth.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The selected lipid biomarkers were significantly reduced in PTB conditions ( Figure 6 ). According to the results of previous research in our laboratory, polar metabolites increase in PTB [ 28 ], but most of the lipid biomarkers tend to decrease in PTB. Among the phospholipids selected as biomarkers, not only PCs and PEs, but also PlsPCs and PlsPEs, were decreased in preterm birth.…”
Section: Resultsmentioning
confidence: 85%
“…Internal standards solution of diacylglycerol (DG, 10:0/10:0), triacylglycerol (TG, 17:0/17:0/17:0), phosphatidylcholine (PC, 10:0/10:0), phosphatidylethanolamine (PE, 10:0/10:0), sphingomyelin (SM, 18:1d/17:0), and ceramide (CER, C17) were diluted with isopropyl alcohol (5 mg/L) and spiked in 30 µL of each CVF sample. The mixed samples were extracted by modified Folch’s method, as described in a previous study [ 28 , 29 , 30 , 31 ]. 300 µL of cold MeOH/CHCl 3 (1:2, v / v ) was added to the CVF sample, and the mixture was sonicated (Daihan Scientific, Seoul, Republic of Korea) for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Ten microliters of N - tert -butyldimethylsilyl- N -methyltrifluoroacetamide (MTBSTFA) along with 1% tert- butyldimethylchlorosilane reagent was added to the vial, derivatized at 80 °C for 30 min, and then cooled at room temperature for 20 min. The final solution was then injected into the GC–MS instrument ( Figure 4 ) [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…This makes it challenging to develop biomarkers for preterm/dysbiotic conditions. Recent studies have shown vaginal metabolites and microbiome profiles could be useful in predicting preterm [55,56]. However, the mechanistic understanding of vaginal microbial genomic factors is needed to develop standard molecular based biomarkers that could aid in early PTB detection.…”
Section: Profiling Of Preterm Associated Gene Clusters In Publicly Av...mentioning
confidence: 99%